2014
DOI: 10.1152/japplphysiol.00074.2014
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training protects against an acute inflammatory insult in mouse epididymal adipose tissue

Abstract: Exercise training reduces systemic and adipose tissue inflammation. However, these beneficial effects seem to be largely tied to reductions in adipose tissue mass. The purpose of the present study was to determine if exercise training confers a protective effect against an acute inflammatory challenge. We hypothesized that the induction of inflammatory markers, such as interleukin 6 (IL-6), suppressor of cytokine signaling 3 (SOCS3), and TNF-α by the beta-3 adrenergic agonist CL 316,243 would be reduced in adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 33 publications
6
44
2
Order By: Relevance
“…In support of our data, others have shown that 6 weeks of VWR 38 and exercise training 30 protect against acute stressors. For example, our group has shown that exercise training offers protection against adipose tissue inflammation induced by the b-3 adrenergic agonist CL 316, 243.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In support of our data, others have shown that 6 weeks of VWR 38 and exercise training 30 protect against acute stressors. For example, our group has shown that exercise training offers protection against adipose tissue inflammation induced by the b-3 adrenergic agonist CL 316, 243.…”
Section: Discussionsupporting
confidence: 92%
“…For example, our group has shown that exercise training offers protection against adipose tissue inflammation induced by the b-3 adrenergic agonist CL 316, 243. 30 In this study, protective effects were primarily observed in eWAT for indices of IL-6 signaling as marked by the mRNA expression of IL-6 and SOCS3, along with the mRNA expression of TNF-a, yet a similar effect did not occur in iWAT. Others 38 have demonstrated that 6 weeks of VWR alters the response to acute tail shock stress in rats.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This compound has been used in other studies to stimulate lipolysis in white adipose tissue. 33,34 30 minutes post-saline or CL injection, inguinal adipose tissue (iWAT) was removed as a representative subcutaneous depot; retroperitoneal (r.p.) adipose tissue was harvested from behind the kidneys as a representative visceral depot.…”
Section: Terminal Surgeries and In Vivo Lipolysis Assessmentmentioning
confidence: 99%
“…In regards to lipolysis and TRPV4, Farias et al [5] reported that continuous swimming training robustly induced ATGL with no effect on CGI-58 protein expression in the epididymal fat of diet-induced obese (DIO) mice. Castellani et al [3] reported that treadmill training reduced TRPV4 protein content in epididymal fat of chow fed mice and the reduction of TRPV4 could mediate the protective effects of prior exercise training against CL 316,243 induced inflammatory status in AT. However, how exercise training will affect TRPV4 and its associated protein expression in adipose tissue of DIO mice remains unclear.…”
Section: Introductionmentioning
confidence: 99%